Research on Multiterminal Current Differential Protection Criterion With High Sensitivity and Synchronization Error Tolerance Capability - Jin, Neng; Lin, Xiangning; Xing, Jiawei; Li, Zhengtian; Liu, Shiming; Chen, Le; Ma, Xiao; Rong, Zirui; Tong, Ning (IEEE transactions on power delivery, 2018)
As the most suitable main protection for multiterminal transmission lines represented by T-connections, current differential protection exhibits great performance due to its high reliability and sensitivity. However, considering multiple substations geographically, there are more severe problems of data synchronization for multiterminal current differential protection than for double-terminal types based on a typical channel. To solve the aforementioned problems, the operating characteristics of multiterminal line differential protection under different synchronization errors on the ρ plane are first analyzed. Based on the influence of synchronization errors on the magnitude and phase of the protection operating value, a design method for the restraint current of multiterminal current differential protection is proposed. To achieve the sensitivity of a high resistance internal fault, as well as the tolerance capability of the data phase-shift error, double restraint coefficients are introduced to optimize the shape and area of the restraint region. Subsequently, the setting method is inferred, which can be used as a reference for an engineering application and the promotion of multiterminal line differential protection. Finally, the simulation results indicate that the proposed method can significantly improve the criterion security for the case of additional data synchronization errors while maintaining the sensitivity of the internal fault.